Sharks from fear to fascination - Wlodarski, Loran; Kleine, Laurie Allen (Florida : Seaworld Inc., 2005)
Discusses the life of sharks, describing where they live, what they eat, how they behave, and how humans study them.
Includes bibliographical references and index.
5.8
3-6.
3-6
Keywords: Sharks -- Juvenile literature; Sharks; Sharks